2021
DOI: 10.1364/ao.416103
|View full text |Cite
|
Sign up to set email alerts
|

Tunable peak power square-wave pulse based on an all-PM thulium-doped mode-locked fiber laser

Abstract: Nanosecond dissipative soliton resonance pulse is a demonstration of an all polarization-maintaining (PM) thulium-doped fiber laser in a nonlinear amplifying loop mirror (NALM)-based figure-eight configuration. Each loop of the apparatus includes a controllable power amplifier. With increased amplifier power, pulse width broadens linearly from 3.6 to 13.5 ns, and maximum single pulse energy can reach 27.5 nJ. Interestingly, the output peak power presents two completely opposite proportional effects in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The RF spectrum with a larger span of at least 1 GHz is shown in Figure 13d to validate the DSR mechanism with modulation envelope. [ 230 ] The highest pulse energy was achieved as high as 0.91 nJ at the maximum pump power of 350 mW as illustrated in Figure 13e.…”
Section: Mode‐locked Fiber Lasermentioning
confidence: 96%
“…The RF spectrum with a larger span of at least 1 GHz is shown in Figure 13d to validate the DSR mechanism with modulation envelope. [ 230 ] The highest pulse energy was achieved as high as 0.91 nJ at the maximum pump power of 350 mW as illustrated in Figure 13e.…”
Section: Mode‐locked Fiber Lasermentioning
confidence: 96%
“…Since Richardson et al observed square pulses in a mode-locked fiber laser in 1991 [6], researchers began to study square pulses. There are different explanations for the formation of square pulses, one of which is dissipative soliton resonance (DSR) [7]. Under the DSR mechanism, the width and energy of the square pulses increase monotonically with the increase of the pump power without wave breaking, and the peak amplitude is almost unchanged [8,9].…”
Section: Introductionmentioning
confidence: 99%